Measurement of the cross section and angular correlations for associated production of a Z boson with b hadrons in pp collisions at root s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (2013)
A study of proton-proton collisions in which two b hadrons are produced in association with a Z boson is reported. The collisions were recorded at a centre-of-mass energy of 7TeV with the CMS detector at the LHC, for an integrated luminosity of 5:2 fb-1. The b hadrons are identified by means of displaced secondary vertices, without the use of reconstructed jets, permitting the study of b-hadron pair production at small angular separation. Differential cross sections are presented as a function of the angular separation of the b hadrons and the Z boson. In addition, inclusive measurements are presented. For both the inclusive and differential studies, different ranges of Z boson momentum are considered, and each measurement is compared to the predictions from different event generators at leading-order and next-to-leading-order accuracy. Copyright CERN.